Indentation characteristics of glass/glass-nanocomposites in Fe-based alloys - Kumari S.; Kumar Lal Das A.; Mandal R.K. (My University, 2025)
Four iron-based alloys with ability to form glasses/glass-nanocomposites were synthesized through Cu-mould casting process. They were subjected to melt-spinning to get glass/glass-nanocomposites. The X-ray diffraction studies of as cast alloys reveal formation of Fe11Mo6C5 (mC44), α-Fe (cI2), Fe5C2 (mC28), Fe3C (oP116), Fe3W3C (cF112), and Cr7C3 (oP40) structure types. The melt-spun ribbons give rise to the formation of glassy phase as well as glass-nanocomposites depending on alloy composition. Samples processed through these two routes display hardness values in the range of ∼ 9 to ∼ 13GPa at 100 g load. Shear bands are observed in case of melt spun ribbons. © 2024